Ironing out the iron profile in heart failure patients: A single centre, outpatient-based cross-sectional study in South Africa - Gerber, A.; Asmal, T.; Barrett, C.L. (SA Heart Journal, 2025)
Background: Iron deficiency is the most common nutritional deficiency globally, affecting up to 55% of patients with heart failure. Iron deficiency is an independent predictor of poor outcomes in heart failure patients. Screening for iron deficiency is recommended by the European Society of Cardiology (ESC) and adopted locally. Objectives: To provide insight into the burden of iron deficiency in patients with heart failure in South Africa by measuring the iron profile and analysing differences in the iron profile between sexes and subgroups of heart failure. Methods: A single-centre descriptive cross-sectional study was performed. Demographic, clinical, echocardiographic and laboratory data of patients with heart failure attending Universitas Academic Hospital in Bloemfontein for 3 months in 2023 were collected and analysed. Results: We included 147 patients, 127 of whom had iron profile results. Over half (60.6%, 77/127) had iron deficiency, while the majority (74.0%, 57/77) had nonanaemic iron deficiency. Iron deficiency was more prevalent in females than males (p-value = 0.0006). Conclusion: A high prevalence of iron deficiency in heart failure was noted. Even though their haemoglobin levels were normal, most patients were iron deficient. Routine screening of heart failure patients, as adopted from the ESC Guidelines 2021, is recommended.